Case Report: Autoimmune Encephalitis Associated With Anti-glutamic Acid Decarboxylase Antibodies: A Pediatric Case Series - Ren, Changhong; Ren, Haitao; Ren, Xiaotun; Zhang, Weihua; Li, Jiuwei; Dai, Lifang; Guan, Hongzhi; Fang, Fang (Frontiers in Neurology, 2021)
Background: Antibodies against glutamic acid decarboxylase (GAD) are associated with various neurologic conditions described in patients, including stiff person syndrome, cerebellar ataxia, refractory epilepsy, and limbic and extralimbic encephalitis. There have been some case reports and investigations regarding anti-GAD65 antibody-associated encephalitis in adult populations, but pediatric cases are rare. We retrospectively analyzed the clinical data of 3 anti-GAD65 antibody-positive patients to explore the diversity and clinical features of anti-GAD65 antibody-associated pediatric autoimmune encephalitis. Methods: The clinical data of a series of 3 patients positive for anti-GAD65 antibody were retrospectively analyzed. GAD65 antibodies were determined in serum and CSF using a cell-based assay. Results: All 3 patients were female, and the onset ages were 4 years and 9 months, 6 years and 16 years old. Their clinical phenotypes included autoimmune limbic encephalitis, extralimbic encephalitis, encephalitis combining limbic and extralimbic encephalitis. The clinical symptoms included seizures, memory deficits, drowsiness, dysautonomia and headache. All patients had abnormal carinal MRI and EEG. All patients received immunotherapy and had transiently good responsiveness, but one patient then experienced relapse. In follow-up, one patient with extralimbic encephalitis recovered completely, while two patients with limbic involvement had poor outcomes with refractory focal epilepsy. Conclusion: In addition to limbic encephalitis, extralimbic encephalitis is also an important phenotype in patients who are positive for anti-GAD65 antibodies. Early diagnosis and immunotherapy can improve the symptoms. However, patients with limbic encephalitis often have refractory epilepsy in the chronic phase and have a poor long-term outcome.